Using meaningful listening activities to increase eighth grade students oral production at Victoria Torres de Neira school - Erazo Herrera, Andrés Eduardo (2017)
All over the world, speaking English immediately opens opportunities, because it is recognized as the language of science and the most useful language in many countries. Most of the information found on the internet such as health, science and others is in English and it let you feel the cultures of the world like no other language. On the other hand, due to the impact of the international culture, the Ecuadorian government requires his population to increase the level of English in B1 or B2, according to the Common European Framework Reference. However, the curriculum in the public system only includes five hours per week in high schools which as we all know, are not enough to enhance English properly. Besides that, it is important to mention that the public area does not include English in elementary schools at all. As a result of that, when they graduate from high school, their knowledge of English is Elementary. In contradistinction to students who graduate from private schools, their English knowledge is at least Upper-Intermediate…..